ANALISIS KUALITAS BUTIR SOAL TES BUATAN GURU MATA PELAJARAN MATEMATIKA KELAS X SMA NEGERI 1 AIRMADIDI TAHUN AJARAN 2019/2020 - Tilaar, Anetha Lyta Flora; Sulangi, Victor R; Pelealu, Eyrene (JSME (Jurnal Sains, Matematika & Edukasi), 2020)
ABSTRACT. This research aims to describe the quality of teacher-made tests on mathematics. This quantitative descriptive research conducted at SMA Negeri 1 Airmadidi, where 100 answer sheets of mathematics test of 10th graders from 3 parallel classes were taken as the sample. Aspects analyzed including the itemâ€™s level of difficulty, validity, reliability, and discrimination index, as well as the effectiveness of distractors. Results found that out of 15 multiple choice items; there was 1 valid question, 14 were invalid, while all of the 5 essay questions were valid. The multiple-choice item's index of reliability of 0.27, which falls in a low category, while the essay questions have the reliability of 0.88, which is categorized as very high; 9 questions have easy in difficulty; 6 questions with moderate difficulty, while all of 5 essay questions were medium; 8 questions have good distractors, and 7 questions were ineffective; 13 questions have good discrimination power and 2 questions have poor discrimination. Two essay questions have a medium discrimination index and 3 questions have good; 5 essay questions were valid, reliable and have a moderate level of difficulty. So, it concluded that the mathematics test made by a teacher for 10th graders at X SMA Negeri 1 Airmadidi generally poor in its quality.Â Key Words: Quality of Test, Reliability, Validity